MODEL OPTIMASI DALAM PENJADWALAN PRODUKSI KERAJINAN PELEPAH PISANG (STUDI KASUS : KUB ANGGREK DESA ASKA) - Nurfadillah, Nurfadillah; Hikmah, Aulia Nurul; Wahyuni, Yuyun; Nurhaliza, Nurhaliza; Fatimah, Sri Putri; Nasbar, Nasbar (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
KUB Anggrek is a joint business group engaged in creative economic activities, namely producing handicrafts from banana fronds located in Aska Village, South Sinjai District, Sinjai Regency.Some of the products produced are bossara, fruit bins, trash cans, jars, bags, and tissue boxes.The purpose of this study is to optimize profits in the production of banana frond handicrafts in Aska Village.The purpose of this study is to optimize profits in the production of banana frond handicrafts at KUB Anggrek Desa Aska. To obtain maximum profit, the right formula is needed through.One of the methods that can be used in linear programming is the simplex method which serves to find the optimum solution that has two or more variables. Optimum solution that has two or more decision variables. Based on the results of linear programming analysis of the amount of banana leaf craft production obtained optimal profit formula Z = 100.000X1 + 30.000X2 +65.000X3 +15.000X4+ 50.000X5 + 45.000X6.From the simplex method calculation, it can be concluded that Aska Village Orchid KUB will get maximum profit if it increases bossara production (X1) by 6.66?7 pieces and increases fox glue inventory (S2) by 0.33 kg each time.